The Effect of Local Wisdom-Based Educational and Recreational Physical Activities Supported by Interactive Multimedia on Students’ Physical Literacy in Physical Education - Hikmah Lestari; Widya Handayani; Iwan palentina; Yulian Supradinata; Tiyo Irawan (Universitas Nahdatul Ulama Surabaya, 2026)
Physical literacy has become an essential concept in physical education as it integrates physical competence, motivation, and confidence, and knowledge and understanding necessary for lifelong physical activity. However, physical education learning in many schools still focuses primarily on motor skills, with limited integration of culturally relevant activities and digital learning media. This study aimed to examine the effects of educational and recreational physical activities, supported by interactive multimedia, on students’ physical literacy. This research employed a quantitative approach using a quasi-experimental design with a pretest–posttest control group. The study was conducted in three junior high schools in Palembang, South Sumatra, Indonesia, involving 60 students. Data were collected through a physical literacy assessment instrument covering physical competence, motivation and confidence, and knowledge and understanding. The data were analyzed using descriptive statistics, normalized gain (N-Gain), and an independent samples t-test with a significance level of 0.05. The results showed a substantial improvement in students’ physical literacy scores, with the mean pretest score increasing from 58.27 (SD = 7.02) to 92.90 (SD = 4.06) on the posttest. The N-Gain value of 0.83 indicated a high level of improvement, and the statistical test confirmed a significant difference between pretest and posttest scores (p < 0.05). These findings indicate that educational and recreational physical activities based on local wisdom supported by interactive multimedia effectively enhance students’ physical literacy in physical education learning.